(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the diagnostic accuracy of CT scan in detecting the gallbladder malignancy taking histopathology as gold standard. METHODOLOGY: this study consisting of 132 cases was conducted at Department of Diagnostic Radiology, Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore during the period from 15 Jan 2025 to 15 April 2025. The age range was 30–70 years with clinical suspicion of GBC underwent CT imaging. Histopathological examination was performed after surgical excision. Diagnostic accuracy parameters including sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: CT showed 89.8% sensitivity, 72.7% specificity, 86.8% PPV, 78.1% NPV, and an overall diagnostic accuracy of 84.1%. Diagnostic performance was higher in older patients and those with BMI >25. Gender-based analysis revealed higher sensitivity in females and greater specificity in males. Conclusion: CT is a reliable, non-invasive tool for diagnosing gallbladder malignancy, with high sensitivity and moderate specificity. Stratified performance indicates its enhanced utility in specific subgroups. Combining CT findings with histopathology, CEUS, and emerging technologies like AI may further improve diagnostic precision